Methodology of culture maintenance and inoculum development for production of solvents by Clostridium acetobutylicum : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Biotechnology at Massey University - Gutierrez, Noemi A (Massey University, 1985)
Various methods of culture maintenance and inoculum development were evaluated for their effectiveness in conserving and improving the property of 2 strains of Clostridium acetobutyicum, namely NCIB 2951 and NRRL B-594, to produce solvents by fermentation of whey permeate. The majority of the methods were effective in maintaining the viability and solventogenic property of the organism. However, since in some cases the viability was maintained but the solventogenic property was not, it is clear that the latter should be used as the index in determining the storage life and time of reprocessing of the stock culture. The methods of culture maintenance investigated included refrigeration at 4°c in distilled water, in phosphate buffer and in Cooked Meat Medium containing glucose ( CMMG) ; by freezing at -20°c in distilled water and in phosphate buffer; by drying in soil and by lyophilization ( freeze drying); and by periodic transfer in CMMG and in whey permeate containing yeast extract. Maintenance of the stock cultures at -20° C in distilled water was found to be the most efficient for the storage stability of both strains of organism. The viability and the potential to produce high solvent concentrations, primarily butanol were maintained without any significant loss after 9 months and 12 months, for strain NCIB 2951 and strain NRRL B-594, respectively. The criteria important for a commercial fermentation, i.e., sugar utilization, yield and butanol production rate, remained stable during storage by this method. It was observed that periodic transfer was a poor method as the culture lost their solventogenic property despite remaining viable. The other preservation methods were not as satisfactory as freezing in distilled water at -20°c since the fermentation ability degenerated to some extent after 9 months of storage. Therefore, after such a period reprocessing of the stock cultures kept by these methods is necessary to revive the cultures and minimize degeneration. The repeated use of the stock cultures was found to be deleterious and should be avoided. The inoculum development procedure investigated to maximize fermentation efficiency included the conventional heat shocking of the stock culture; variation in the number of culture stages; use of gassing as an index of transfer time; and the use of different levels of inoculum size. The strain differences which exist between NRRL B-594 and NCIB 2951 influenced how the inocula from these strains should be propagated prior to fermentation. Strain NRRL B-594 responded to heat shocking while strain NCIB 2951 did not. Neither ethanol nor butanol treatment of the stock cultures of the latter were advantageous. Using a 3-stage inoculum development procedure, the fermentation efficiency of strain NRRL B-594 was improved by employing heat shocking at 80C for 15 min in the revival stage of the stock culture. The germination factors for the spores of NCIB 2951 await identification. However, by using the presence of highly motile cells as an index in transferring from the revival stage, the inoculum development procedure resulted in a significantly higher butanol concentration value and production rate. Thus, the revival stage was the most critical.
Keywords: Clostridium acetobutylicum; Solvents; Bacteriology; Cultures and culture media